Fungitoxic non-glycosidic iridoids from Alibertia macrophylla - Young, M.Claudia M.; Braga, Marcia R.; Dietrich, Sonia M.C.; Gottlieb, Hugo E.; Trevisan, Ligia M.V. [UNESP]; Bolzani, Vanderlan da Silva [UNESP] (Elsevier, 1992)
The aqueous alcohol extract of the leaves of Alibertia macrophylla afforded two epimeric pairs of iridoid aglycones and one of them showed high inhibitory activity against Aspergillus niger, Cladosporium sphaerospermum, C. cladosporioides and Colletotrichum gloesporioides. Three of the compounds are reported for the first time from natural sources. Their structures were established on the basis of spectroscopic studies, mainly through 13C NMR analysis. © 1992.
Keywords: Alibertia macrophylla; antifungal activity.; non-glycosidic iridoids; Rubiaceae